Making School-Based Children’s Mental Health Screening A National Priority in Post-War Liberia - Peter C. Dossen (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
Children’s mental health remains one of Liberia’s most urgent and under-addressed public health challenges. Post-war trauma, extreme poverty, and inadequate infrastructure have exposed millions of children to emotional and behavioral risks, yet Liberia lacks a national policy framework for early identification and intervention. Despite the national mental health policy commitments, the implementation of school-based mental health services has been limited and fragmented. The purpose of this opinion-based policy perspective is to emphasize the magnitude of children’s mental health problems in Liberia, explain the importance of school-based universal mental health screening as a potential early identification and intervention approach, and provide possible recommendations to implement universal screening approach as a national priority to promote children’s mental health for optimum lifelong functioning. To conclude, a series of short-, medium-, and long-term policy recommendations, centered on intersectoral coordination, culturally adapted screening tools, teacher training, and national monitoring systems, are proposed based on international evidence and grounded in local realities. The recommendations highlight sustainable actions to integrate mental health screening into routine school operations, strengthen early identification, and improve the long-term cognitive, emotional, and physical well-being of the next generation.